Akibat Hukum Pemenang Lelang Dan Kesalahan Membuat Akta Risalah Lelang - Muhammad Afif Boby Wijaya; Edith Ratna M.S. (Notarius, 2022)
The minutes of auction are binding authentic evidence, the legality of an auction document. The purpose of this research is to see and analyze the legal consequences if the auction participants who have been declared winners of the auction do not fulfill their obligations within a predetermined time limit. As well as to find out and analyze the legal consequences if the Class II Auction Officer had an error when compiling the auction minutes deed. The method used in this research is juridical empirical by conducting field studies. This research finds that auction participants who have become auction winners do not fulfill their obligations within the stipulated time limit, there are sanctions imposed on the auction buyers, in accordance with Article 50 paragraph (5) of the Regulation of the Minister of Finance No. 40 / PMK.07 / 2006. If the Class II Auction Officer has an error when compiling the auction minutes deed, it can be corrected immediately and there is no write-off of any existing mistakes, if it is correct then printing is done..Keywords: Minutes of Auction Deed; Collateral Object; Auction OfficerAbstrakRisalah lelang merupakan bukti otentik yang mengikat, keabsahan suatu dokumen lelang. Tujuan dalam penelitian yakni guna melihat serta menganalisa akibat hukum jika peserta lelang yang sudah dinyatakan menjadi pemenang lelang tak memenuhi kewajiban hingga batas waktu yang sudah ditetapkan. Serta untuk mengetahui dan menganalisis akibat hukum apabila Pejabat Lelang Kelas II terdapat kesalahan ketika menyusun akta risalah lelang. Metode yang dipakai pada penelitian yakni Yuridis Empiris dengan melakukan studi lapangan. Penelitian ini menemukan bahwa peserta lelang yang sudah menjadi pemenang lelang tak memenuhi kewajiban hingga batas waktu yang sudah ditetapkan, terdapatnya sanksi yang dijatuhkan ke pembeli lelang, sesuai dengan Pasal 50 ayat (5) Peraturan Menteri Keuangan No. 40 / PMK.07 / 2006. Apabila Pejabat Lelang Kelas II terdapat kesalahan ketika menyusun akta risalah lelang bisa langsung dilakukan perbaikan dan tidak terdapat pencoretan terhadap kekeliruan yang ada, jika telah tepat barulah dilakukan pencetakan.Kata Kunci: Akta Risalah Lelang; Objek Jaminan; Pejabat Lelang